Governmental and Non-Governmental Community Practice—What's the Difference?. (13th May 2021) - Itzhaki-Braun, Yael; Feldman, Guy; Frankenburg, Ruth; Karassik, Daniel; Schreiber, Keren
Abstract: The social work profession emphasises the importance of social workers' involvement in community practice, which aims to promote social policy and social change via peoples' organising and acting. The current qualitative study compares between the perceptions and everyday experiences of governmental and non-governmental community social workers. Drawing on in-depth interviews with twenty-six community social workers in the public social services and non-governmental organisations in Israel, findings highlight similarities and differences along three main themes: (i) community social workers' constructions of their professional role, referring to soft community practice verus radical community practice and to aspects of influence; (ii) the tension between the professional freedom they hold and the limitations imposed on them; and (iii) professional position within the organisation and the field of community social work. We discuss these findings in light of the theoretical perspectives of perception of organisational politics and emotional labour. Implications to community practice are outlined.